Proyectos de comunicación para el desarrollo en España: importancia, formación de profesionales en la materia y expectativas de futuro - Bernabé Fraguas, Javier (Revista Española de Desarrollo y Cooperación, 2023)
This article deals with one of the less analyzed issues in Spain within the communication for development: communication´s projects. It emphasizes its importance and the necessity of having well trained human resources for its draft and implementation, working also on a typology, pointing out the little interest showed by most of the Spanish NGOs for Development and advancing and studying two subjects in depth.